The Merck index : an encyclopedia of chemicals, drugs, and biologicals - O'Neil, Maryadele J.; Heckelman, Patricia E.; Dobbelaar, Peter H.; Roman, Kristin J.; Kenny, Catherine M.; Karaffa, Linda S. (Royal Society of Chemistry, 2013)
The Merck Index is the definitive reference work for scientists and professionals looking for authoritative information on chemicals, drugs and biologicals. It has been the leading source of information on chemical compounds for generations of scientists and professionals, selling over one million copies since its publication in 1889. The Merck Index contains over 10,000 monographs with information relating to compounds of significance in research, commerce and environmental impact. The 15th edition, available from Royal Society of Chemistry publishing for the first time, is fully revised and updated and contains over 500 new monographs. Over 35% of the existing entries have been updated since the last edition, molecular weights have been recalculated with the latest IUPAC standards and there are revised periodic table and atomic weight tables. The Merck Index is an essential reference for all scholarly and professional chemists, biochemists, pharmacists and toxicologists and of interest to students, teachers, academic libraries, academic researchers, information professionals, solicitors, journalists and government agencies.